2020
DOI: 10.1088/1748-0221/15/09/p09004
|View full text |Cite
|
Sign up to set email alerts
|

The ABC130 barrel module prototyping programme for the ATLAS strip tracker

Abstract: silicon pixel, silicon strip and transition radiation sub-detectors, will be replaced with an all new 100 % silicon tracker, composed of a pixel tracker at inner radii and a strip tracker at outer radii. The future ATLAS strip tracker will include 11,000 silicon sensor modules in the central region (barrel) and 7,000 modules in the forward region (end-caps), which are foreseen to be constructed over a period of 3.5 years. The construction of each module consists of a series of assembly and quality control step… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 24 publications
4
30
0
Order By: Relevance
“…The analogue currents remain constant at approximately 70 mA, regardless of the radiation dose delivered to the ASIC. This is consistent with what was observed for ABC130 ASICs [6]. The digital currents see an initial increase in current, reaching a maximum of 140 mA at 1 Mrad before decreasing to 60 mA at higher doses.…”
Section: Current Measurementssupporting
confidence: 91%
See 1 more Smart Citation
“…The analogue currents remain constant at approximately 70 mA, regardless of the radiation dose delivered to the ASIC. This is consistent with what was observed for ABC130 ASICs [6]. The digital currents see an initial increase in current, reaching a maximum of 140 mA at 1 Mrad before decreasing to 60 mA at higher doses.…”
Section: Current Measurementssupporting
confidence: 91%
“…During the December beam test, where two new ABCStar V1 ASICs (273 and 274) were irradiated alongside two previously tested ASICs (259 and 267), a comparable current measurement shows a similar increase of the digital current for the new ASICs, as shown in figure 10b). The two previously irradiated ASICs show a digital current increase much lower than the unirradiated ASICs, confirming the effect of pre-irradiation on the TID bump observed for ABC130 ASICs [6]. The piece-wise behaviour of the digital current curves is a result of stopping/starting data collection runs.…”
Section: Current Measurementssupporting
confidence: 71%
“…complied with module performance requirements [2], but are smeared over the full range of latencies between DC-DC switching and triggering and therefore average over any time-dependent effects. Since the noise increase was assumed to be caused by the EMI noise emitted from the DC-DC circuitry, an additional time-resolved study of the observed noise increase and the DC-DC switching was performed.…”
Section: Jinst 16 P06012mentioning
confidence: 99%
“…The assembly procedures follow closely those described in ref. [13]. For the miniaturized sensors, four ABCStar chips and one HCCStar chip were glued onto a prototype hybrid made of low-mass flexible copper-polyimide PCB.…”
Section: Readout Chipsmentioning
confidence: 99%